Methods of lowering the glycemic index of food and their underlying mechanisms - a review - Patrycja Sornek; Wiktoria Izdebska; Jakub Stanek; Klaudia Perkowska; Anna Kaźmierczak; Anna Mich; Igor Pawlak; Agata Borkowska; Radosław Ciesielski; Anna Kiełb (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose of review: The term glycemic index (GI) is the measure of how much a specific substance increases the postprandial blood glucose level [1]. Substances with lower GI promote a lower glycemic response and are said to promote satiety, postprandial insulin secretion and maintain insulin sensitivity and therefore help to control blood glucose concentrations [2]. According to guidelines on the management of patients with diabetes, type 2 diabetes mellitus patients' source of carbohydrates in diet should be whole grain cereal products especially with low GI [3].  Type 2 diabetes is a chronic, metabolic disease occurring mostly in adults. It leads to numerous chronic complications that include e.g. macroangiopathy, retinopathy, nephropathy, neuropathy and diabetic foot as well as vulnerability to infections [2]. These complications lower the quality of life, generate costs when treating them and eventually lead to death.  Currently there are about 422 million people with diabetes worldwide and the number is expected to rise [3]. Therefore it is crucial for patients to maintain their blood glucose at stable levels to prevent progression of the disease and its complications. The glycemic response can be modified by implementing a low GI diet. The aim of this study is to provide an overview of selected strategies lowering the glycemic index and the probable mechanisms by which they work.   Methods: For this review, articles in the Pubmed and Google Scholar databases were analyzed as well as the references of previously found articles. Current state of knowledge: Existing studies show that some strategies alter the glycemic index and glycemic response that can help diabetic patients to better control their glucose blood level. Summary: This review summarizes studies concerning methods of lowering the glycemic index and mechanisms of action of those specific methods.